(untitled) (Journal of Advanced Veterinary and Animal Research, 2014)
The process of programmed cell death, or apoptosis, is generally characterized by distinct morphological characteristics and energy - dependent biochemical mechanisms. Apoptosis is a widely conserved phenomenon helping many processes, including normal cell turnover, proper development and functioning of the immune system, hormone dependent atrophy etc. Inappropriate apoptosis (either low level or high level) leads to many developmental abnormalities like, neurodegenerative diseases, ischemic damage, autoimmune disorders and many types of cancer. To use cells for therapeutic purposes through generating cell lines, it is critical to study the cell cycle machinery and signalling pathways that controls cell death and apoptosis. Apoptotic pathways provide a fundamental protective mechanism that decreases cellular sensitivity to damaging events and allow proper developmental process in multi-cellular organisms. Major mediator of apoptosis is a family of proteins known as caspases. There are mainly fourteen types of caspases but out of them only ten caspasese have got essential role in controlling the process of apoptosis. These ten caspases have been categorized into either initiator caspases (caspase 2, 8, 9, 10) or executioner caspases (caspase 3, 6, 7). Although various types of caspases have been identified so far, the exact mechanisms of action of these groups of proteins is still to be fully understood. The aim of this review is to provide a detail overview of role of different caspases in regulating the process of apoptosis. http://dx.doi.org/10.5455/javar.2015.b52